2007
DOI: 10.1002/ijc.23242
|View full text |Cite
|
Sign up to set email alerts
|

Differences in antitumor effects of various statins on human pancreatic cancer

Abstract: Statins are widely used for the treatment of hypercholesterolemia. However, their inhibitory action on HMG-CoA reductase also results in the depletion of intermediate biosynthetic products, which importantly contribute to cell proliferation. The aim of the present study was to compare the effects of the individual commercially available statins on experimental pancreatic cancer. The in vitro effects of individual statins (pravastatin, atorvastatin, simvastatin, lovastatin, cerivastatin, rosuvastatin and fluvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 61 publications
6
100
2
1
Order By: Relevance
“…Further, in Capan-2 cells, decreased levels of NFB and its downstream target, survivin, were induced by atorvastatin. These data suggest that under conditions used here atorvastatin readily induced effects that can be explained by an inhibited prenylation in Capan-2 cells [7], but not in the Panc-1 and the MIA PaCa-2 cell lines.…”
Section: Atorvastatin Affects Raf/mek and Nfκb Pathways In Capan-2 Cellsmentioning
confidence: 61%
See 2 more Smart Citations
“…Further, in Capan-2 cells, decreased levels of NFB and its downstream target, survivin, were induced by atorvastatin. These data suggest that under conditions used here atorvastatin readily induced effects that can be explained by an inhibited prenylation in Capan-2 cells [7], but not in the Panc-1 and the MIA PaCa-2 cell lines.…”
Section: Atorvastatin Affects Raf/mek and Nfκb Pathways In Capan-2 Cellsmentioning
confidence: 61%
“…Thus, fluvastatin was shown to enhance the antiproliferatory effect of gemcitabine in MIA PaCa-2 pancreatic cancer cells [5]. Besides their in vitro effects, statins have been shown to inhibit pancreatic tumor growth in vivo [3,5,7]. In a recent study performed on nude mice it was shown that different statins decreased the tumor growth of transplanted Capan-2 cells [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Statins not only inhibit cholesterol synthesis but also prevent isoprenoid formation and decrease the membrane translocation and activation of the small GTPases and their downstream effectors by inhibiting mevalonate synthesis via blocking HMG-CoA reductase (Alegret & Silvestre 2006, Katsiki et al 2009). The effect of statins on cancer cells has been a subject of numerous studies (Zhong et al 2003, Campbell et al 2006, Gbelcová et al 2008. Statins show antineoplastic activity by inhibiting proliferation and activating apoptosis or autophagy in various cancer cell lines (Bifulco et al 1999, Sassano & Platanias 2008, Parikh et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies demonstrated antineoplastic effects of statins (Campbell et al 2006, Sivaprasad et al 2006. The antiproliferative effects of statins were demonstrated in in vitro studies on hepatocellular carcinoma (Kawata et al 1994), lung (Hawk et al 1996), breast (Campbell et al 2006), and pancreatic cancer cells (Gbelcová et al 2008). These effects appear to be generated either via effects on cell cycle and induction of growth suppression or via induction of apoptosis of malignant cells (Sassano & Platanias 2008).…”
Section: Introductionmentioning
confidence: 99%